Effect of sport specialization in judo and kayak on trunk stability - Barbado, D.; Juan Recio, C.; López Valenciano, A.; Elvira, J. L. L.; Dieën, J. H. V.; Vera Garcia, F. J. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Effect of sport specialization in judo and kayak on trunk stability Introduction: Trunk/core stability is considered an important determinant of athletic performance in sports with large demands on balance control (van Dieën et al., 2012). However, studies on the effect of specialization in sports with these demands on trunk stability are lacking. The aim of this study was to compare trunk stability measures between judokas, kayakers and recreational athletes. Methods: 25 competitive judokas, 10 competitive kayakers and 36 recreational athletes took part in this study. A battery of static and dynamic tests was performed to measure trunk balancing while sitting on stable and unstable seats placed on a force plate (Kistler 9286A). Postural and dynamic sway were assessed by analyzing the mean radial displacement of the centre of pressure (COP). Sudden and unexpected trunk loads in anterior, posterior and lateral directions, were applied to the thorax by a pneumatic mechanism while the subject was seated with the pelvis fixed. Trunk angular displacement was measured and the damping and stiffness coefficients of the trunk were calculated from the first 110 ms of data after perturbation. Results: Judo athletes showed higher trunk stiffness and lower angular displacement after lateral loading than recreationally trained individuals (p<0.05). Kayakers showed lower mean radial displacements of the COP than judokas and recreational athletes, especially in dynamic balance tasks on the unstable seat (p<0.05). Discussion: Judokas` trunk response after lateral loading and Kayakers` high trunk balance control while sitting may be related to the specific exertions they do regularly while training and competing, i.e.: judokas undergo rapid lateral and rotational loads in upright stance during defensive and offensive techniques, and Kayakers must maintain balance in the kayak to reduce hydrodynamic friction while kayaking. Therefore, sport specific tests appear to be necessary to properly characterize trunk stability in competitive athletes.